Electrochemical and Photoelectrochemical Water Splitting: Operando Raman and Fourier Transform Infrared Spectroscopy as Useful Probing Techniques. Issue 3 (6th January 2023) - AlSalka, Yamen; Schwabe, Sven; Geweke, Jan; Ctistis, Georgios; Wackerbarth, Hainer
Abstract : The urgent need for the clean energy transition of our society is the incentive for the scientific research groups to further advance the development of green hydrogen production. The field of (photo)electrochemical water splitting is currently experiencing a significant expansion of scientific investigations. Despite the technological and material development brought by this technique, the complex reaction mechanisms on the surface of (photo)electrodes during water splitting have led to considerable scientific questions and many contradictions to theoretical expectations. Therefore, a deeper tracking of the surface‐active centers, the experimental reaction mechanisms, and the nature of intermediates requires the use of in situ spectroscopic techniques. In this review, operando Raman and Fourier transform infrared (FTIR) spectroscopies in the field of (photo)electrochemical water splitting are presented. In the first section, the environmental challenges and possible solutions are discussed, and then the principle of vibrational spectroscopy and its applications in the field of (photo)catalysis are presented in detail. In the second part, the recent results of operando Raman and FTIR techniques for (photo)electrochemical water splitting, including challenges and reaction mechanisms, are reviewed. To simplify the presentation, the results are subdivided according to the materials used as (photo)electrodes. Abstract : Vibrational spectroscopy is a powerful operando technique in an electrochemical device during cycling to probe the reaction mechanisms and identify the surface intermediates. Numerous studies have recently been published studying electrodes for water splitting in situ. This review focuses on operando Raman and attenuated total reflection‐Fourier transform infrared spectroscopy as useful tools to understand electrochemical/photoelectrochemical water splitting.